The space-time trellis codes with improved performance for fading channels. (8th June 2012) - Jin, Ik Soo
The one motivation of this work stems from the different design criteria between in slow fading channels and in fast fading channels. We presented a new 4-PSK 4-state STTC with two transmit antennas for slow fading channels by improving the design parameters of the code. The other motivation of this work stems from the application of new mapping to STTC to obtain a further performance improvement. We refer the new mapping as proportional mapping. The 8-state 8-PSK STTC with proportional mapping is presented. From the simulation results, it is shown that new code is superior to the corresponding TSC code and the BBH code over slow fading channels. It is also shown that in case of 8-state 8-PSK STTC, proportional mapping outperforms Gray mapping and natural mapping over fast Rician fading channels.